Melatonin Induces Parthenocarpy by Regulating Genes in Gibberellin Pathways of ‘Starkrimson’ Pear (Pyrus communis L.) - Liu, Jianlong; Zhai, Rui; Liu, Fengxia; Zhao, Yingxiao; Wang, Huibin; Liu, Lulu; Yang, Chengquan; Wang, Zhigang; Ma, Fengwang; Xu, Lingfei (Frontiers in Plant Science, 2018)
Parthenocarpy, the production of seedless fruit without fertilization, has a variety of valuable qualities, especially for self-incompatible species, such as pear. To explore whether melatonin (MT) induces parthenocarpy, we used ‘Starkrimson’ pear as a material for morphological observations. According to our results, exogenous MT promoted the expansion and division of the mesocarp cells in a manner similar to hand pollination. However, the seeds of exogenous MT-treated fruit were undeveloped and aborted later in the fruit-setting stage. To further investigate how MT induced parthenocarpy, we studied changes of related hormones in the ovaries and found that MT significantly increased the contents of the gibberellins (GAs) GA3 and GA4. Thus, paclobutrazol (PAC), a GA-biosynthesis inhibitor, was used to study the relationship between GAs and MT. In addition, spraying MT after treatment with PAC did not increase GA content nor lead to parthenocarpy. Through a transcriptome analysis, we discovered that MT can cause significant upregulation of PbGA20ox and downregulation of PbGA2ox. However, no significant difference was observed in PbGA2ox compared with the control after PAC and MT applications. Thus, MT induces parthenocarpy by promoting GA biosynthesis along with cell division and mesocarp expansion in pear.